Dihydroartemisinin remodels macrophage into an M1 phenotype via ferroptosis-mediated DNA damage - Li, Liu-Gen; Peng, Xing-Chun; Yu, Ting-Ting; Xu, Hua-Zhen; Han, Ning; Yang, Xiao-Xin; Li, Qi-Rui; Hu, Jun; Liu, Bin; Yang, Zi-Yi; Xu, Xiang; Chen, Xiao; et al. (Frontiers in Pharmacology, 2022)
Lung cancer recruits tumor-associated macrophages (TAM) massively, whose predominantly pro-tumor M2 phenotype leads to immunosuppression. Dihydroartemisinin (DHA) has been proven to remodel TAM into an anti-tumor M1 phenotype at certain concentrations in the present study, which was hypothesized to facilitate anti-lung cancer immunotherapy. However, how DHA remodels the TAM phenotype has not been yet uncovered. Our previous work revealed that DHA could trigger ferroptosis in lung cancer cells, which may also be observed in TAM thereupon. Sequentially, in the current study, DHA was found to remodel TAM into the M1 phenotype in vitro and in vivo. Simultaneously, DHA was observed to trigger ferroptosis in TAM and cause the DNA damage response and NF-κB activation. Conversely, DHA-induced DNA damage response and NF-κB activation in TAM were attenuated after inhibition of ferroptosis in TAM using an inhibitor of ferroptosis. Importantly, a ferroptosis inhibitor could also abolish the DHA-induced phenotypic remodeling of TAM toward M1 phenotype. In a nutshell, this work demonstrates that DHA-triggered ferroptosis of TAM results in DNA damage, which could activate downstream NF-κB to remodel TAM into an M1 phenotype, providing a novel strategy for anti-lung cancer immunotherapy. This study offers a novel strategy and theoretical basis for the use of traditional Chinese medicine monomers to regulate the anti-tumor immune response, as well as a new therapeutic target for TAM phenotype remodeling.